El concepto de lo bello y el uso del arte como mecanismo de afrontamiento del estrés en estudiantes de pregrado de la Universidad de Antioquia (2012)
ABSTRACT: Art psychology is a discipline that tries to give answer to phenomenon like psyche developing, symbols use and creation or subjective use of art. In this investigation was applied a test to 40 students of Antioquia University, of these 20 are students from Arts College and 20 are students from another academic dependences, this with the objective of investigate if the named group of subjects use the art for make front to stressful situations. In this investigation is evident influence that can have the family, the environment and the academy in the establishment of the beauty concept and the utility that each subject finds to art.